John Chrysostom ’On the Incomprehensible Nature of God’ – The Simpler Way of Presenting Complex Theological and Philosophical Issues - Kochańczyk-Bonińska, Karolina (Vox Patrum, 2023)
The purpose of this paper is to indicate how, that is, with the help of which means, Chrysostom in his five homilies “On the Incomprehensible Nature of God” introduces his community in Antioch to the intricacies of the dispute with the Anomoeans, as far as the possibility of knowing God and his essence are concerned. The main differences between those texts and other fundamental polemical sources with Eunomius will also be taken under consideration. John uses both biblical and philosophical terms to underline the negative aspect of theology and his five homilies are not so theologically and philosophically sophisticated as Basil’s or Gregory’s texts, unlike even Gregory of Nazianzus, whose Orations, have a similar overall message. John uses methods adequate to accomplish his goal, which is to preserve the orthodox concept and unify the Antiochian Church.